2020
DOI: 10.3390/plants9050580
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation Potential of Crop Plants in Countering Nickel Contamination in Carbonation Lime Coming from the Sugar Industry

Abstract: The phytoremediation potential of four crop species cultivated on carbonation lime coming from the sugar industry with water-soluble nickel (Ni) exceeding the Italian legal limit of 10 µg L−1 was assessed. Two autumn–winter species (spinach and canola) were tested with and without the addition of bentonite in a greenhouse experiment in order to overcome prolonged unfavourable weather conditions. Two spring-summer species (sunflower and sorghum) were grown in outdoor boxes. Plant species were selected among cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Attapulgite and bentonite, generally, limited the root absorption of Ni. De Bernadi et al [53] confirmed that bentonite amendment sequesters Ni and, thus, reduces its bioavailability. Kumararaja et al [49] found that pillared bentonite stabilized heavy metals in soil and reduced absorption by plants, particularly, at a dosage of 2.5% (w/w) (one of the dosages considered in this study).…”
Section: Discussionmentioning
confidence: 96%
“…Attapulgite and bentonite, generally, limited the root absorption of Ni. De Bernadi et al [53] confirmed that bentonite amendment sequesters Ni and, thus, reduces its bioavailability. Kumararaja et al [49] found that pillared bentonite stabilized heavy metals in soil and reduced absorption by plants, particularly, at a dosage of 2.5% (w/w) (one of the dosages considered in this study).…”
Section: Discussionmentioning
confidence: 96%
“…40 The addition of bentonite also reduced the bioavailable Ni in lime and wastewater. 20,41 This is typical of clay minerals, which reduce the bioavailable properties of heavy metals as they adsorb these metals onto their surfaces. 13,19 Vetiver is also tolerant to Zn, absorbing up to 10 000 mg/kg within 30 days with a high translocation factor.…”
Section: Discussionmentioning
confidence: 99%
“…14,16,17 Considering the negative effects of heavy metals on the environment, several technologies have been identified for managing heavy metal polluted sites. Of these technologies, phytoremediation is a cost-effective and environmentally friendly option 18 , and there is growing interest in the application and optimisation of phytoremediation 19,20 . Vetiver grass (Chrysopogon zizanioides) is a terrestrial plant that has been adapted for soil and water remediation purposes because it is easily propagated, with rapid growth and can survive in extreme climatic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…De Bernardi et al [ 36 ] directed their research toward testing the phytoremediation potential of four crop species for nickel (Ni) in order to sustain the application of green clean-up techniques suitable for the remediation of Ni-contaminated sites. The legal threshold for water-soluble Ni in soil, set by Italian Legislative Decree 186/2006, is 10 µg L −1 [ 37 ].…”
Section: Highlights Of the Special Issuementioning
confidence: 99%